Historical aspects of pear cultivation in the Caucasus - I. A. Bandurko; Z. Sh. Daguzhieva (Вестник Майкопского государственного технологического университета, 2025)
Abstract. The relevance. The Caucasus is one of the richest world centers of origin: more than 260 species of 37 genera of wild fruit and berry plants grow here. Such diversity has served as the basis for the widespread development of horticulture. In the scientific literature it is noted that horticulture in this region is over 3000 years old. The abundance of species and forms of pear has contributed to the creation of an original local assortment of this valuable crop, distinguished by its originality in various environmental conditions. Many local varieties of pear have not only economic and scientific value, but are also a historical heritage of our country.The problem of the research is that many varieties of Caucasian pear are currently little known, preserved in the collections of scientific institutions and in amateur gardening. The goal is to study the process of the emergence of local varieties of pear and the development of horticulture in the Caucasus. The research methods used are general scientific ones (analysis, comparison, generalization, synthesis), source study and historical-comparative methods.The results of the research: historical aspects of the creation of a pear assortment in various regions of the Caucasus have been considered, the importance of preserving the gene pool of local pear varieties for practical use and as an object for students' research activities and educational work has been substantiatedKey conclusions: an appeal to the historical experience of creating and developing gardens will help to replenish data on the regional history of pear cultivation and use them in the work to identify, preserve and use old Circassian varieties.